STAGE: A spatio-temporal attention and graph embedding framework for modeling human mobility trajectories - Sizhe Zhang; Xinyu Zhang; Yunhan Jiang; Patrick Fowler; Michael Podgursky; Guangli Zhang; Kenan Li; Nan Lin (Spatial Statistics, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Estimation of root zone water storage capacity (Sr) in natural ecosystems subject to high interannual climate variability - Maryam Khorami; Gary J. Sheridan; Keirnan Fowler; Patrick N.J. Lane (Journal of Hydrology, 2026)

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Phylogenomics reveals extreme gene tree discordance in a lineage of dominant trees: hybridization, introgression, and incomplete lineage sorting blur deep evolutionary relationships despite clear species groupings in Eucalyptus subgenus Eudesmia - Todd G.B. McLay; Rachael M. Fowler; Patrick S. Fahey; Daniel J. Murphy; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Molecular Phylogenetics and Evolution, 2023)

Phylogeography and classification of Dusty Miller (Spyridium parvifolium; Rhamnaceae): a morphologically variable shrub from south-east Australia - Catherine Clowes; Rachael Fowler; Patrick Fahey; Jürgen Kellermann; Gillian Brown; Michael Bayly (Plant Systematics and Evolution, 2023)
Spyridium parvifolium is a widespread and morphologically variable shrub from south-eastern Australia. Several varieties have been recognised, and there is disagreement on the accepted taxonomy between Australian states. This study investigated the phylogeography of the species and assessed genetic distinctiveness of its morphological variants. Nuclear ribosomal DNA and complete chloroplast genomes from seventy-two samples of S. parvifolium and seven samples from closely related species were sequenced and analysed using both Bayesian and maximum likelihood phylogenetic methods. The results showed incongruence in the placement of several associated taxa ( S. cinereum , S. obcordatum and S. daltonii ), plausibly due to long branch attraction, introgression or incomplete lineage sorting. Spyridium parvifolium was resolved as paraphyletic in both phylogenies, with accessions from west of the Murray Darling Depression divergent from those east of the Depression. We found evidence of isolation within S. parvifolium on the inland side of the Great Dividing Range and recent gene flow across Bass Strait. The variants of S. parvifolium were not supported as genetically distinct, and with the prevalence of several variants at single sites and morphological intergrades between variants, we conclude that the taxon is a single, morphologically variable species and that no infraspecific classification is warranted.

Use of plastid genome sequences in phylogeographic studies of tree species can be misleading without comprehensive sampling of co-occurring, related species - Patrick S. Fahey; Rachael M. Fowler; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Tree Genetics & Genomes, 2021)

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Characterization of Behavioral, Signaling and Cytokine Alterations in a Rat Neurodevelopmental Model for Schizophrenia, and Their Reversal by the 5-HT6 Receptor Antagonist SB-399885 - Sinead E. Shortall; Ola H. Negm; Maxine Fowler; Lucy C. Fairclough; Patrick J. Tighe; Peter M. Wigmore; Madeleine V. King (Molecular Neurobiology, 2018)

Mobile receivers: releasing the mooring to ‘see’ where fish go - Sean A. Hayes; Nicole M. Teutschel; Cyril J. Michel; Cory Champagne; Patrick W. Robinson; Melinda Fowler; Tina Yack; David K. Mellinger; Samantha Simmons; Daniel P. Costa; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

Low-temperature acclimation of barley cultivars used as parents in mapping populations: response to photoperiod, vernalization and phenological development - Allen Limin; Ann Corey; Patrick Hayes; D. Brian Fowler (Planta, 2007)